Position Tracking Control Of Slider Crank Mechanism Using Fuzzy PID Controller - Haris, Sharil Izwan (UTeM, 2016)
Slider crank mechanism (SCM) is an arrangement of mechanical parts which are consist of the slider, connecting rod and crank. It is designed to convert straight-line motion to rotary motion or vice versa and is widely used in engineering fields such as the combustion engine, water pump, compressor and robotics. This research focused on the kinematic anal ysis of SCM that studying the tracking position control. Both simulation and experimental method have been done to achieve the research target. In the simulation, the proportional-integralderivative (PID) controller is presented with the enhancement by fuzzy logic control, in order to make the controller strategy more adaptive. The experiment was carried out with hardware in the loop simulation (HILS) to examine the controller performance. The simulation result show that the performance of PID with fuzzy logic control is more robust than the PID controller in variable parameters. Experimental results have proven the effectiveness of proposed controller. In general , it can be concluded that the Fuzzy PID controller ha superior tracking performance in position control of SCM. With the intention of enhancing the controller performance, some recommendations have been highlighted.